Diversity and distribution of MHC class I and II alleles in chicken populations worldwide. (October 2022) - Martin, Rebecca; Tregaskes, Clive; Kaufman, Jim
Abstract : Almost everything known about antigen processing and presentation outside of mammals is from work on chickens. In contrast to mammals, unusually strong genetic associations exist between MHC haplotype and responses to infection in chickens. These associations, at least in part, seem to be due to the expression of a single classical class I and II molecule in most tissues. Unlike in mammals, chicken TAP and tapasin genes are highly polymorphic. Furthermore, peptide translocation specificity is very similar to the peptide binding specificity of the dominantly expressed MHCI molecule in each haplotype. These genes appear to be co-evolving – a process made possible by strong linkage disequilibrium across the 'minimal essential MHC'. Similar co-evolution with the chaperone DM has been proposed for the single dominantly expressed class II gene. This study aimed to begin the most complete and exhaustive analysis of global MHC population genetics outside of humans. Once haplotypes have been defined by their class I and II alleles, interesting haplotypes would be selected for more detailed studies. Illumina MiSeq was used with a novel double-barcoding system to perform multiplexed amplicon se- quencing of exons 2 and 3 from all classical class I and class II loci. Samples were obtained from all major commercial breeders, 'fancy' breeds and free-range local chickens from Ethiopia, Nigeria, Tan- zania and Ghana. Our results show that, globally, there is huge diversity in chicken MHC alleles, most of which has never previously been reported from studies on experimental lines. Commercial flocks, however, have extremely low diversity, suggesting that artificial selection and population bottlenecks have had a drastic effect on the immune phenotypes of commercial flocks. These populations of commercial birds are also enriched in haplotypes with apparently promiscuous class I alleles that bind a wide variety of peptides and confer resistance to many common infectious diseases.